2017
DOI: 10.3389/fpls.2017.01990
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fig (Ficus carica L.) Fruit Color: Metabolomic and Transcriptomic Analyses of the Flavonoid Biosynthetic Pathway

Abstract: Combined metabolomic and transcriptomic analyses were carried out with fig cultivar Green Peel and its color mutant “Purple Peel.” Five and twenty-two metabolites were identified as having significantly different contents between fruit peels of the two cultivars at young and mature stages, respectively. Cyanidin O-malonylhexoside demonstrated a 3,992-fold increase in the mature purple peel, the first identification of a major cyanidin in fig fruit; cyanidin 3-O-glucoside, cyanidin O-malonylhexoside O-hexoside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
161
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(173 citation statements)
references
References 71 publications
10
161
1
1
Order By: Relevance
“…As [18]. In this study, 119 kinds of differential flavonoid-related metabolites were found (including 10 kinds of anthocyanins).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As [18]. In this study, 119 kinds of differential flavonoid-related metabolites were found (including 10 kinds of anthocyanins).…”
Section: Discussionmentioning
confidence: 61%
“…A study on green and purple asparagus suggested that the difference in color was mainly caused by the contents of peonidin and cyanidin and their glycoside derivatives [17]. Metabolomic analysis the color difference of fig peel showed that the content of anthocyanin derivatives in purple peel was significantly higher than that in green fruit [18]. These results indicate that metabolomics is an important and effective method to analyze the formation mechanism of plant color.…”
Section: Introductionmentioning
confidence: 92%
“…Plant metabolomics can yield a large amount of qualitative and quantitative data on metabolites according to the organism-specific metabolic pathways, metabolic networks, and functions that the metabolites participate in; thus, biologically meaningful data can be retrieved [13]. Plant metabolomic studies have been of value for the identification of metabolites, regional differences, natural variations, and intraspecific and interspecific differences in citrus fruits [14,15], figs [16], and tomatoes [17]. Therefore, plant metabolomics can be a good tool to improve upon plant research.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the techniques for detecting metabolites were mainly depended on single technique such as column chromatography, gas chromatography (GC) and liquid chromatography (LC), then the integrated approaches like gas chromatograph-mass spectrometer (GC-MS) and liquid chromatograph-mass spectrometer (LC-MS) became promising tools for the study of plant metabolites diversity [20,21]. Recently, more advanced technique LC-Electrospray Ionization−tandem mass spectrometry (LC-ESI-MS/MS) has emerged and been widely used in flavonoids study [22][23][24]. Nowadays, the relationship between differential metabolites profiles and biochemical properties could be analyzed based on the advanced metabolomics techniques [24].…”
mentioning
confidence: 99%
“…The cutting edges of metabolomics approaches allow more accurate and precise identification of metabolites in biosynthetic pathway. Significant different metabolites in flavonoid biosynthetic pathway were reported in purple fig mutation compared to the green control [23]. The interaction of the primary and secondary metabolites profiles combined with proteomics elucidated the accumulation of phenolic substances and other major compounds related to flavonoids accumulation during seed development in cacao [25].Over the past decade, studies related to red-fleshed apple were mainly focused on the structural and regulatory genes which play important roles in anthocyanins biosynthesis [26][27][28][29].…”
mentioning
confidence: 99%